MARKET ORIENTATION AND TAKAFUL NONFINANCIAL PERFORMANCE: A STRATEGY? - Norizan Remli; Wan Norhayate Wan Daud (International Journal of Accounting, Finance and Business, 2020)
Strategies that improve performance draw the attention of managers. The IslamicInsurance industry in Malaysia requires an emphasis on customer orientation and interfunctionalcoordination to improve and achieve better performance. This paper discusses themarket orientation and its components, the relationship between market orientation andnonfinancial performance, and the implication of the market orientation strategy within theTakaful industry in Malaysia. Future research on a similar topic is recommended to improve acertain area such as a combination of nonfinancial and financial performance study to providefurther proof of the positive impact of market orientation on the performance of Takafulbusiness in Malaysia.